Re-modelling scientific change: complex systems frames innovative problem solving - Hooker, Cliff (Lato Sensu: Revue de la Société de philosophie des sciences, 2018)
Complex systems are used, studied and instantiated in science, with what consequences? To be clear and systematic in response it is necessary to distinguish the consequences, (i) for science, of science using and studying complex systems, (ii) for philosophy of science, of science using and studying complex systems, (iii) for philosophy of science, of philosophy of science modelling science as a complex system. Each of these is explored in turn, especially (iii). While (iii) has been least studied, it will be shown how modelling science as a complex process may change our conception of science and thereby query what a philosophy of science adequate to this complexity might look like.